A Mesoscopic Model with Vectorial Structure Parameter for Interacting Star Polymers. Issue 1 (18th December 2017) - Fitzgerald, Barry W.; Briels, Wim J.
Abstract: An updated mesoscopic model for transient forces between two star polymers is presented. Calculation of the transient forces is based on the response of a vectorial structure parameter between two star polymers and differs from previous models that used a scalar structure parameter. The update of the model is motivated by the occurrence of two distinct processes in previous small‐scale simulations of two star polymers moving past each other. A simple model that takes these processes into account turns out to fit into an obvious generalization of the RaPiD model introduced by us some time ago. The model reproduces forces from the simulation quite well, and at the same time removes an unphysical feature of the RaPiD model used so far. Abstract : An updated mesoscopic model is presented here to describe transient forces between star polymers and is based on the response of a vectorial structure parameter between the polymers. This model is motivated by the occurrence of two distinct processes observed in earlier small‐scale simulations. The model reproduces forces from simulation quite well and fits easily within the scheme of the previous coarse‐grained models.